Pengaruh E-Learning terhadap Motivasi Belajar Mahasiswa Ilmu Komunikasi IBI Kwik Kian Gie - Kristianto, Raymond; Nuraryo, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The development of information technology in the digital era has driven a transformation in learning from traditional face-to-face methods to more flexible and innovative approaches, one of which is e-learning. This study aims to examine the effect of using e-learning as a learning communication medium on students’ learning motivation. The study is grounded in Stimulus–Response theory as its theoretical framework. A quantitative method with a survey approach was employed by distributing questionnaires to students of the Communication Science Program at the Kwik Kian Gie Institute of Business and Informatics (IBI Kwik Kian Gie) who use e-learning in the learning process. The data were analyzed using regression techniques with the assistance of SPSS software. The results show a coefficient of determination of 0.645, indicating that the use of e-learning accounts for 64.5% of the variance in students’ learning motivation. These findings indicate that e-learning as a learning communication medium has a significant and effective influence on enhancing the intrinsic learning motivation of Communication Science students at IBI Kwik Kian Gie.